2016
DOI: 10.2105/ajph.2016.303172
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Ages of Legal Access for Tobacco in the United States From 1863 to 2015

Abstract: In the United States, state laws establish a minimum age of legal access (MLA) for most tobacco products at 18 years. We reviewed the history of these laws with internal tobacco industry documents and newspaper archives from 1860 to 2014. The laws appeared in the 1880s; by 1920, half of states had set MLAs of at least 21 years. After 1920, tobacco industry lobbying eroded them to between 16 and 18 years. By the 1980s, the tobacco industry viewed restoration of higher MLAs as a critical business threat. The ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…In 2015, approximately 4.7 million middle and high school students in the US were current tobacco smokers [ 2 ]. Nine out of ten of smokers begin smoking before age 18, and smoking behavior among young adults is predictive of smoking in later years [ 1 , 3 , 4 ]. Despite evidence of tobacco industry marketing toward youth and young adults, [ 5 ] policies to reduce access to tobacco for this group have been limited in scope [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, approximately 4.7 million middle and high school students in the US were current tobacco smokers [ 2 ]. Nine out of ten of smokers begin smoking before age 18, and smoking behavior among young adults is predictive of smoking in later years [ 1 , 3 , 4 ]. Despite evidence of tobacco industry marketing toward youth and young adults, [ 5 ] policies to reduce access to tobacco for this group have been limited in scope [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…While marijuana use is illegal by federal laws, but in states with marijuana laws, using marijuana is protected. Although no minimum legal age has been established for marijuana, the minimal legal age for purchasing tobacco at age 18 (36) may affect marijuana use and marijuana-cigarette transitions. In addition, the MML in the U.S. may increase acceptability to and reduce the perceived harm from marijuana, and it may also increase the availability and accessibility of marijuana among adolescents (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…To understand the arguments for raising the minimum legal access age for tobacco to 21 years, one must first examine the history of tobacco policy. Laws setting a minimum legal access age first began to appear in the 1880s in the United States . Some states had set that age as low as 16 at that time, but as the turn of the century came, there was growing concern about children using tobacco .…”
mentioning
confidence: 99%
“…Laws setting a minimum legal access age first began to appear in the 1880s in the United States . Some states had set that age as low as 16 at that time, but as the turn of the century came, there was growing concern about children using tobacco . Apollonio and Glantz found that in 1920, 46 of the 48 states had a minimum legal access age and at least 14 states had set that age limit of 21 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation